Sustainability analysis of lubricant oils for minimum quantity lubrication based on their tribo-rheological performance. (15th October 2017) - Pereira, O.; Martín-Alfonso, J.E.; Rodríguez, A.; Calleja, A.; Fernández-Valdivielso, A.; López de Lacalle, L.N.
Abstract: Nowadays, environmentally friendly cutting fluids should be applied in manufacturing processes. Concretely, in many machining processes the use of minimum quantity of lubrication (MQL) is established as common routine. In this paper, the use of natural biodegradable oils as an alternative to traditional canola oils used in MQL is analyzed, comparing five different alternatives (i.e.: sunflower oil, high oleic sunflower oil, castor oil and ECO-350 recycled oil). Firstly, the aim is to evaluate the feasibility of the proposed oils, just analyzing their tribological and rheological characteristics. Secondly, a full battery of experimental tests was performed in order to validate their behavior during cutting Inconel 718, a difficult-to-cut material commonly used in aeronautical components. Finally, life cycle assessment was carried out with the aim of analyzing their environmental feasibility. Results show that the combination of low viscosity with high friction coefficient implies an increase in tool life. In this line, ECO-350 recycled oil presents a feasible behavior and improves the tool life up to 30% in comparison with commercial canola oil. However, its recycling process has to be improved from an environmental point of view. Taking both issues, high oleic sunflower oil presents a balance between them. On one hand, it improves tool life (15%) and on the other hand, similar environmental impact is obtained compared with canola oil. This supposes an advance, being more efficiently, not only environmentally speaking but also technically. Highlights: A review of biodegradable oils applied to machining processes is presented. Tribological and rheological analysis of four natural oils and canola commercial oil are performed. MQL lubrication with different oils analyzed was applied to Inconel 718 end milling. LCA was carried out in which canola oil, high oleic sunflower oil and ECO-350 oil use during machining was analyzed.